IMPLEMENTASI PEMBANGUNAN KEPARIWISATAAN DI TAMAN MARGASATWA MANGKANG KOTA SEMARANG - Arina Pramudita; Hesti Lestari; Susi Sulandari (Journal of Public Policy and Management Review, 2013)
Regional Technical Implementation Unit (UPTD) in the park wildlife Mangkang Semarang City is the agency which manages one of attraction in Semarang City area. Management of this attraction as a form of Policy Implementation of Tourism Development in Semarang City based on District Regulation Semarang City Number 3 of 2010. The research was carried out using the theory of policy implementation George Edward III with several factors that influence that is communication, resource, attitudes so that can be obtained an exact description of the development implementation of the park wildlife as a form of implementation the tourism development. This study used qualitative descriptive approach as the unit of analysis, while the data collection techniques obtained through interviews with informants,documentation and observation.The result of this study indicated that the development of tourism by UPTD Wildlife Areas Mangkang have not been optimal. It looks from stil lack the number of visitors, the public complaints regarding the completeness of the existing facilities at the wildlife park until the issue of socialization and less intensified tourism promotion.The concluction that can be derived that the development of tourism by UPTD Wildlive Areas Mangkang have not been optimal. Therefore, there needs to be new techniques in the management and development tourism. For examples: improvement of animal enclosures in the accordance with the capacity of the number of animals, completing tourist facilities and informating of wildlife parks is more intense and effective.